Epidemiology and Antibiotic Resistance of Combat Wound Infection in Surgical Patients - Pavlo L. Byk; Ihor H. Kryvorchuk; Ivan M. Leshchyshyn; Nikita S. Martyniuk; Dmytro Yu. Orlov (Ukrainian Journal of Cardiovascular Surgery, 2024)
The aim. To analyze the microbiological spectrum of pathogens causing surgical site infections and their antibiotic resistance in surgical patients injured during the military conflict between Ukraine and Russia.Materials and methods. This study was based on 137 bacteriological examinations of biological samples from patients treated in the surgical department of the Kyiv City Oleksandrivska Clinical Hospital in 2022. The samples included 81cultures isolated from postoperative wounds and 56 cultures from the abdominal cavity. Susceptibility to antibacter drugs was determined according to the European Committee on Antimicrobial Susceptibility Testing (EUCAST) standards. Statistical analysis was performed using IBM SPSS Statistics.Results. Among the 137 analyzed samples, the most common pathogens were Klebsiella pneumoniae (22.6%), Enterococcus faecalis (13.1%), Staphylococcus epidermidis (13.1%), Pseudomonas aeruginosa (11.6%), and Escherichia coli (10.2%). In the abdominal cavity samples (n = 56), E. coli was predominant (17.9%), followed by K. pneumoniae (16.1%), E. faecalis (16.1%), S. epidermidis (10.7%), Candida (8.9%), and P. aeruginosa (7.1%). In postoperative wound samples (n = 81), K. pneumoniae was found in 27.2%, P. aeruginosa in 14.8%, S. epidermidis in 14.8%, S. aureus in 12.3%, and E. faecalis in 11.1%.K. pneumoniae showed high resistance to amikacin (86.6%), meropenem (74.2%), piperacillin-tazobactam (82.8%), and ceftriaxone (86.2%). E. faecalis exhibited resistance to imipenem (58.8%), levofloxacin (47.1%), and vancomycin (12.5%). S. epidermidis had resistance to gentamicin (13.3%), meropenem (50%), and oxacillin (35.7%). P. aeruginosa demonstrated resistance to ciprofloxacin (45.6%), meropenem (67.4%), ceftazidime (52.3%), and piperacillin-tazobactam (48.7%).Conclusion. The primary pathogens causing surgical site infections in military surgical patients are K. pneumoniae, E. faecalis, S. epidermidis, P. aeruginosa, and E. coli. The pathogen spectrum varies between abdominal cavity infections and postoperative wound infections. There is a clear trend towards increased detection of antibiotic-resistant pathogens, particularly among military personnel. Colonization with resistant microorganisms increases during medical evacuation through different levels of the evacuation chain.